2018
DOI: 10.1542/hpeds.2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Diagnostic Test Use and Associated Outcomes in Staphylococcal Scalded Skin Syndrome at Children’s Hospitals

Abstract: For children hospitalized with SSSS, lower use of diagnostic tests was not associated with changes in outcomes. Hospitals with high diagnostic test use may be able to reduce testing without adversely affecting patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…We chose not to include regimens with third‐generation cephalosporins or ampicillin, which may have limited the number of included neonates, because these antibiotics are frequently administered during evaluation for invasive bacterial infections 23 . We found a very low occurrence of treatment failure in our study cohort across all three groups, which is consistent with other studies of SSSS that report an overall good prognosis and low recurrence and/or readmission rates 6,16,24 . The low prevalence of treatment failure, however, precluded our ability to detect small differences among antibiotic regimen groups that may exist.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We chose not to include regimens with third‐generation cephalosporins or ampicillin, which may have limited the number of included neonates, because these antibiotics are frequently administered during evaluation for invasive bacterial infections 23 . We found a very low occurrence of treatment failure in our study cohort across all three groups, which is consistent with other studies of SSSS that report an overall good prognosis and low recurrence and/or readmission rates 6,16,24 . The low prevalence of treatment failure, however, precluded our ability to detect small differences among antibiotic regimen groups that may exist.…”
Section: Discussionsupporting
confidence: 70%
“…Children with complex chronic medical conditions as classified by Feudtner et al 17 were excluded, since these children may require a different treatment approach than the general pediatric population. In order to decrease diagnostic ambiguity, we excluded children if an alternative dermatologic diagnosis was recorded as a principal or secondary diagnosis (eg, Stevens‐Johnson syndrome or scarlet fever) 16 . Finally, hospitals with fewer than 10 children with SSSS during the study period were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies from the United States used a similar approach to our study but in pediatric ED 17 and inpatient settings. 36,37 For instance, Florin et al 17 evaluated variation in the use of diagnostic tests and its association with hospital admission and 3-day ED revisits in children presenting with community-acquired pneumonia across 36 pediatric hospitals in the United States. The study found 3 ED groups based on test use, including low, moderate, and high test users.…”
Section: Sensitivity Analysesmentioning
confidence: 99%